Fracture evolution in oil-rich rhyolitic lavas of the Hailar Basin, northeastern China. (February 2021) - Zheng, Han; Mao, Anqi; Chen, Wei; Zhu, Defeng
Abstract: Rhyolitic lavas can hold considerable oil exploration potential which is inferred to be controlled by fracture systems. The need for a better understanding of fracture properties and related petroleum systems for such rocks is the principal motivation of this study. We investigate the fracture evolution of this play type by an analysis of the Early Cretaceous oil-rich rhyolitic lava outcrops, located in the Hailar Basin, northeastern China, integrating multiscale fracture data from field investigation, optical microscopy, fluorescence imaging, and scanning electron microscopy. Six main types of volcanic-related and tectonism-induced fractures are identified. Aperture, spacing, and length of these fractures predominantly show power-law distributions, and in most cases, the dimension of these three parameters follows that columnar joints > platy cooling fractures ≈ tectonic fractures ≫ conjugate shear fractures ≫ perlitic fractures. In addition, the fracture orientation patterns are commonly predictable. Small fractures usually make significant porosity contribution and are excellent reservoir spaces, while large fractures control the permeability and act as channels. The early Early Cretaceous NW–SE extension (D2 of the five phases of basin deformation) dominated the fracture evolution of the lavas. Although the seal of the reservoir is probably not extensively damaged by the reactivation of fractures during the multistage deformation of the basin, the likelihood of reactivation of fracture sets C1, C3, and T1 needs to be carefully evaluated during the exploration and recovery, as the reactivation tendency factors ( f a ) of these sets are > 1 at a certain stage of deformation. We suggest that the observed patterns may be extrapolated to similar rhyolitic lavas in many parts of the world. Highlights: Fracture types, geometries, and origins are deciphered. Most small fractures are excellent reservoir spaces. Large fractures control the permeability. Fracture reactivation tendency is evaluated.